A 1992 Social Accounting Matrix (SAM) for Tanzania - International Food Policy Research Institute (International Food Policy Research Institute, 2008)
This dataset is a 1992 social accounting matrix (SAM) for Tanzania. On the basis of recently generated national accounts data, a 56 sector SAM was built focusing on the disaggregation of the agricultural sectors - comprising 21 of the 56 sectors. For a description of the construction and use of this dataset, download the Trade and Macroeconomics Division Discussion Paper Number 30.